Discrimination within Recognition Memory in Schizophrenia - Scott R. Sponheim; Melanie M. Blahnik; Kathryn A. McGuire (Behavioral Sciences, 2013)
Episodic memory is one of the most affected cognitive domains in schizophrenia. First-degree biological relatives of individuals with schizophrenia also have been found to exhibit a similar, but milder, episodic memory deficit. Unlike most studies that focus on the percent of previously presented items recognized, the current investigation sought to further elucidate the nature of memory dysfunction associated with schizophrenia by examining the discrimination of old and new material during recognition (measured by d') to consider false recognition of new items. Using the Recurring Figures Test and the California Verbal Learning Test (CVLT), we studied a sample of schizophrenia probands and the first-degree biological relatives of patients with schizophrenia, as well as probands with bipolar disorder and first-degree biological relatives to assess the specificity of recognition memory dysfunction to schizophrenia. The schizophrenia sample had poorer recognition discrimination in both nonverbal and verbal modalities; no such deficits were identified in first-degree biological relatives or bipolar disorder probands. Discrimination in schizophrenia and bipolar probands failed to benefit from the geometric structure in the designs in the manner that controls did on the nonverbal test. Females performed better than males in recognition of geometric designs. Episodic memory dysfunction in schizophrenia is present for a variety of stimulus domains and reflects poor use of item content to increase discrimination of old and new items.